Preparation method and application of ternary positive electrode material coated with carbon quantum dots and MOF
Modifying the ternary cathode material by coating carbon quantum dots and MOFs is solved, and the problems of poor structural stability and limited electrochemical performance are achieved, and higher charge and discharge specific capacity, cycle stability and rate performance are achieved.
Patent Information
- Application Number
- CN202510300461.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
AI Technical Summary
The existing ternary positive electrode materials have poor structural stability during charging and discharging, and the side reaction between the surface and the electrolyte leads to rapid capacity decay, which limits its application.
The ternary cathode material is modified by coating carbon quantum dots and MOFs, and the structural stability and electrochemical properties of the material are improved by using the conductivity of carbon quantum dots, the high specific surface area and abundant active sites of MOFs.
It significantly improves the structural stability and electrochemical performance of the ternary positive electrode material, including improving the charge and discharge specific capacity, cycle stability and rate performance, and extends the cycle life of the battery.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion batteries, and in particular relates to a preparation method and application of a ternary positive electrode material coated with carbon quantum dots and MOF. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their high energy density, long cycle life, and no memory effect. x Co y Mn z O2 (x+y+z=1) has become one of the hot topics in current research due to its high specific capacity and working voltage. However, there are some problems with ternary cathode materials during the charge and discharge process, such as poor structural stability and rapid capacity decay caused by side reactions between the surface and the electrolyte, which limits their further application.
[0003] To solve these problems, the ternary cathode materials are usually modified by coating. MOF materials have high specific surface area, adjustable pore size and abundant active sites. Coating them on the surface of ternary cathode materials can effectively improve the structural stability and interface performance of the materials. At the same time, carbon quantum dots have good conductivity, chemical stability and biocompatibility. Coating with MOF is expected to further improve the electrochemical performance of ternary cathode materials. However, there are few studies on the preparation methods and related applications of ternary cathode materials with simultaneous coating of MOF and carbon quantum dots. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a ternary positive electrode material coated with carbon quantum dots and MOF and its application in view of the problems existing in the prior art. The composite material prepared by this method has excellent structural stability and electrochemical properties and can be used in high-performance lithium-ion batteries.
[0005] The purpose of the present invention can be achieved by the following scheme: The present invention provides a method for preparing a ternary positive electrode material coated with carbon quantum dots and MOF, comprising the following steps: S1. Preparation of Carbon Quantum Dots The biomass solution is heated to react to obtain a carbon quantum dot solution; S2. Preparation of MOF precursor solution Dissolving the metal salt and the organic ligand in an organic solvent and stirring evenly to obtain a MOF precursor solution; S3, ternary cathode material coated with MOF and carbon quantum dots The ternary cathode material is added to the carbon quantum dot solution, and ultrasonic dispersion is performed to obtain a mixed solution; then the MOF precursor solution is added to the mixed solution, and the reaction is stirred to obtain a ternary cathode material coated with MOF and carbon quantum dots.
[0006] As an embodiment of the present invention, in step S1, the biomass includes one or more of glucose, sucrose, and starch. The concentration of the biomass solution is 0.1-1 g / mL. The solvent is deionized water.
[0007] As an embodiment of the present invention, in step S1, the temperature of the heating reaction is 180-240° C. and the time is 4-12 hours. The heating reaction is carried out in a high-pressure reactor. After the heating reaction is completed, it is naturally cooled to room temperature, and the resulting solution is filtered through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.
[0008] As an embodiment of the present invention, in step S2, the metal salt includes nickel chloride.
[0009] As an embodiment of the present invention, in step S2, the organic ligand includes 2,3,6,7,10,11-hexamidotriphenyl hexahydrochloride (HATP·6HCl).
[0010] The metal organic framework material MOF [Ni3(HITP)2] obtained by reacting nickel chloride and 2,3,6,7,10,11-hexamidotriphenyl hexahydrochloride (HATP·6HCl) in the present invention has good conductivity, and its theoretical conductivity can reach thousands of S / m (such as 4000 S / m or higher), which is much higher than the conductivity of traditional conductive materials such as activated carbon and porous graphite. At the same time, this MOF material shows good stability under various conditions, especially in electrochemical environments, it can maintain cycle stability, which means that even after multiple charge and discharge processes, its performance will not be significantly reduced.
[0011] As an embodiment of the present invention, in step S2, the organic solvent includes N,N-dimethylformamide (DMF).
[0012] As an embodiment of the present invention, in step S2, the molar ratio of the metal salt to the organic ligand is 1:1-1:3.
[0013] As an embodiment of the present invention, in step S2, the concentration of the metal salt in the MOF precursor solution is 0.05-0.2 mol / L.
[0014] The MOF material of the present invention is added in the form of a precursor solution, rather than being prepared as a MOF material. The corresponding MOF material can be obtained by stirring and reacting the precursor solution at a temperature of 25 - 80 °C for 12 - 48 h. Starting from the precursor solution, in the solution state, it can ensure that the MOF material is uniformly coated on the ternary cathode material, and can better control the coating process of MOF on the surface of the ternary cathode material.
[0015] As an embodiment of the present invention, in step S3, the preparation method of the ternary cathode material: Dissolve nickel salt, cobalt salt, and manganese salt according to the stoichiometric ratio LiNi x Co y Mn z O2 (x + y + z = 1, 0 < x < 1, 0 < y < 1, 0 < z < 1) in deionized water to prepare a mixed solution with a total metal ion concentration of 0.5 - 2 mol / L. Add a precipitant to the mixed solution, stir and react at 40 - 80 °C for 4 - 12 h to obtain a hydroxide precursor precipitate. After filtering, washing, and drying the precipitate, mix it with a lithium source according to the stoichiometric ratio and calcine it at 700 - 1000 °C for 8 - 20 h to obtain the ternary cathode material LiNi x Co y Mn z O2.
[0016] As an embodiment of the present invention, in step S3, the time for ultrasonic dispersion is 30 - 60 min. Ultrasonic dispersion can make the carbon quantum dots uniformly adsorbed on the surface of the ternary cathode material.
[0017] As an embodiment of the present invention, in step S3, the MOF precursor solution is uniformly and slowly dropped into the mixed solution at a rate of 5 - 8 ml / min. The purpose of slow dropping is to enable the MOF to be uniformly coated and react on the surface of the ternary cathode material. If the dropping rate is too fast, it will cause too high a local concentration, resulting in uneven coating of the MOF on the ternary material and affecting the performance of the final composite material.
[0018] As an embodiment of the present invention, in step S3, the temperature for stirring reaction is 25 - 80 °C and the time is 12 - 48 h. The stirring reaction is the reaction for coating MOF on the surface of the ternary cathode material that has adsorbed carbon quantum dots. In this temperature range and under the condition of stirring, the MOF precursors react with each other, gradually forming a coating layer on the surface of the ternary cathode material, and cooperating with the carbon quantum dots to finally form a composite material of the ternary cathode material coated with MOF and carbon quantum dots.
[0019] As an embodiment of the present invention, in step S3, the usage ratio of the ternary cathode material, the carbon quantum dot solution, and the MOF precursor solution is 10-15 g: 100-150 ml: 100-150 ml.
[0020] As an embodiment of the present invention, in step S3, the obtained product is filtered, washed and dried at 60-120° C. for 12-24 hours.
[0021] The present invention adds the ternary cathode material to the carbon quantum dot solution for ultrasonic dispersion, which enables the carbon quantum dots to be uniformly adsorbed on the surface of the ternary cathode material. This uniform adsorption helps the carbon quantum dots to act as an intermediate medium after the subsequent MOF precursor solution is added dropwise, which better promotes the interaction between the ternary cathode material and MOF, and is conducive to the full contact and reaction between the MOF material and the ternary cathode material and the carbon quantum dots, so that the MOF can be effectively coated to form a uniform coating layer. Since the carbon quantum dots themselves have good electrical conductivity, chemical stability and biocompatibility, adding the carbon quantum dots first and evenly distributing them on the surface of the cathode material can improve the conductivity of the cathode material in advance, laying the foundation for the subsequent improvement of electrochemical performance.
[0022] If MOF is directly coated on the surface of the positive electrode material, or on the surface of other coating layers (such as carbon coating layers), the resulting coating structure is not stable enough because it does not cooperate with carbon quantum dots. The structural stability of the ternary positive electrode material is poor during charging and discharging, and the microscopic structure is prone to change. At the same time, the lack of carbon quantum dots will have limited improvement in the electrochemical performance of the positive electrode material, and the efficiency of microscopic processes such as ion and electron transmission is low, and the degree of improvement in electrochemical performance is not as good as the joint coating of the two.
[0023] From the perspective of the entire process and synergy, if carbon quantum dots are added later, it will affect the uniform distribution of carbon quantum dots on the surface of the material. Because after the MOF precursor solution is added first for reaction, the surface state of the material changes. At this time, adding carbon quantum dots may cause the carbon quantum dots to not be adsorbed on the surface of the material as effectively and evenly as when they are added first, thus affecting the overall performance improvement of the composite material, such as it may not be able to play its role in improving the electron transmission rate and enhancing mechanical properties.
[0024] As an embodiment of the present invention, in step S3, the obtained product does not need to be subjected to high temperature treatment.
[0025] From the perspective of material properties, MOF material itself has a high specific surface area, adjustable pore size and abundant active sites. Stirring the reaction at 25 - 60 ° C for 12-48 hours can effectively coat the surface of the ternary positive electrode material and form a good structure. No high temperature is required to promote the reaction or change its morphology to achieve the purpose of coating.
[0026] From the perspective of avoiding material damage, high-temperature calcination may destroy the structure of MOF and the performance of carbon quantum dots. MOF is a metal-organic framework material. High temperature may decompose its organic ligands, causing its structure to collapse and lose its original advantages such as high specific surface area and active sites. Carbon quantum dots may also aggregate or change their structure at high temperatures, affecting their good electrical conductivity, chemical stability and biocompatibility, and thus cannot work with MOF to effectively improve the electrochemical performance of ternary cathode materials.
[0027] The present invention also provides a ternary positive electrode material coated with MOF and carbon quantum dots obtained by the preparation method for use in a lithium ion battery.
[0028] The ternary positive electrode material coated with MOF and carbon quantum dots of the present invention improves the electrochemical performance. The good conductivity of carbon quantum dots can increase the electron transfer rate of the material and reduce the internal resistance of the battery. The high specific surface area and abundant active sites of MOF are beneficial to the infiltration of electrolyte and ion transmission. The two work together to improve the charge and discharge specific capacity, cycle stability and rate performance of the ternary positive electrode material.
[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) Improved structural stability: The MOF coating layer can effectively inhibit the structural changes of the ternary cathode material during the charge and discharge process and improve the structural stability of the material. At the same time, the presence of carbon quantum dots helps to further stabilize the material structure.
[0030] (2) Improved electrochemical performance: Carbon quantum dots have good electrical conductivity, which can increase the electron transfer rate of the material and reduce the internal resistance of the battery. The high specific surface area and abundant active sites of MOF are conducive to the infiltration of electrolytes and ion transport. The synergistic effect of the two significantly improves the charge and discharge specific capacity, cycle stability and rate performance of the ternary cathode material.
[0031] (3) Simple preparation method: The preparation method of the present invention adopts common solution reaction and calcination process, which is simple to operate and easy to industrialize. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with specific embodiments. The following examples are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0033] Example 1 Ternary cathode material LiNi 0.8 Co0.1 Mn 0.1 Preparation of O2: Nickel sulfate, cobalt sulfate, and manganese sulfate were dissolved in deionized water in a stoichiometric ratio to prepare a mixed solution with a total metal ion concentration of 1 mol / L. Sodium hydroxide was added to the mixed solution as a precipitant, and the mixture was stirred at 60°C for 8 h to obtain a hydroxide precursor precipitate. The precipitate was filtered, washed, and dried, and then mixed with lithium carbonate in a stoichiometric ratio and calcined at 850°C for 12 h to obtain the ternary positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0034] Preparation of carbon quantum dots: Glucose was used as the raw material and dissolved in deionized water to prepare a solution with a concentration of 0.5 g / mL. The solution was transferred to a high-pressure reactor and reacted at 200°C for 8 h. After the reaction was completed, it was naturally cooled to room temperature and the resulting solution was filtered through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.
[0035] Preparation of MOF precursor solution: Nickel chloride and 2,3,6,7,10,11-hexamidotriphenyl hexahydrochloride (HATP·6HCl) were dissolved in DMF at a molar ratio of 1:2 to prepare a solution with a nickel chloride concentration of 0.1 mol / L, and the solution was stirred evenly to obtain a MOF precursor solution.
[0036] Ternary cathode material coated with MOF and carbon quantum dots: 10 g of the ternary cathode material obtained in step 1 was added to 100 mL of the carbon quantum dot solution obtained in step 2, and ultrasonically dispersed for 45 min to allow the carbon quantum dots to be uniformly adsorbed on the surface of the ternary cathode material. Then, 100 mL of the MOF precursor solution obtained in step 3 was slowly added dropwise (6 ml / min) to the above mixed solution, and stirred at 40 ° C for 24 h. After the reaction, the obtained product was filtered, washed, and dried at 80 ° C for 18 h to obtain a composite material of ternary cathode material coated with MOF and carbon quantum dots.
[0037] Example 2 Ternary cathode material LiNi 0.6 Co 0.2 Mn 0.2 Preparation of O2: Nickel chloride, cobalt chloride, and manganese chloride were dissolved in deionized water according to a stoichiometric ratio to prepare a mixed solution with a total metal ion concentration of 1.5 mol / L. Ammonia water was added to the mixed solution as a precipitant, and the mixture was stirred at 70°C for 6 h to obtain a hydroxide precursor precipitate. The precipitate was filtered, washed, and dried, and then mixed with lithium hydroxide according to a stoichiometric ratio and calcined at 900°C for 10 h to obtain the ternary positive electrode material LiNi 0.6 Co 0.2 Mn0.2 O2.
[0038] Preparation of carbon quantum dots: Sucrose was used as the raw material and dissolved in deionized water to prepare a solution with a concentration of 0.8 g / mL. The solution was transferred to a high-pressure reactor and reacted at 220°C for 6 h. After the reaction was completed, it was naturally cooled to room temperature and the resulting solution was filtered through a 0.22 μm filter membrane to obtain a carbon quantum dot solution.
[0039] Preparation of MOF precursor solution: Nickel chloride (NiCl2) and 2,3,6,7,10,11-hexamidotriphenyl hexahydrochloride (HATP·6HCl) were dissolved in DMF at a molar ratio of 1:1.5 to prepare a solution with a nickel chloride concentration of 0.15 mol / L, and stirred evenly to obtain a MOF precursor solution.
[0040] Ternary cathode material coated with MOF and carbon quantum dots: 15 g of the ternary cathode material obtained in step 1 was added to 150 mL of the carbon quantum dot solution obtained in step 2, and ultrasonic dispersion was performed for 60 min to allow the carbon quantum dots to be uniformly adsorbed on the surface of the ternary cathode material. Then, 150 mL of the MOF precursor solution obtained in step 3 was slowly added dropwise (6 ml / min) to the above mixed solution, and stirred at 50 ° C for 36 h. After the reaction, the obtained product was filtered, washed, and dried at 100 ° C for 15 h to obtain a composite material of ternary cathode material coated with MOF and carbon quantum dots.
[0041] Comparative Example 1 Preparation of LiNi ternary cathode material without MOF and carbon quantum dots 0.8 Co 0.1 Mn 0.1 O2.
[0042] The preparation method is the same as the preparation steps of the ternary positive electrode material in Example 1.
[0043] Comparative Example 2 Preparation of ternary positive electrode materials coated only with MOF.
[0044] According to the ternary positive electrode material LiNi in Example 1 0.8 Co 0.1 Mn 0.1 The preparation method of O2 obtains a ternary cathode material, which is then added to a MOF precursor solution for coating reaction. Specifically, 10 g of the ternary cathode material is added to 100 mL of the MOF precursor solution obtained in step 3 of Example 1, and stirred at 40°C for 24 h. After the reaction is completed, the obtained product is filtered, washed, and dried at 80°C for 18 h to obtain a ternary cathode material coated only with MOF.
[0045] Comparative Example 3 Preparation of ternary positive electrode materials coated only with carbon quantum dots.
[0046] According to the ternary positive electrode material LiNi in Example 1 0.8 Co 0.1 Mn 0.1 The preparation method of O2 obtains a ternary positive electrode material, which is then added to a carbon quantum dot solution for a coating reaction. The specific operation is as follows: 10 g of the ternary positive electrode material is added to 100 mL of the carbon quantum dot solution obtained in step 2 of Example 1, ultrasonically dispersed for 45 min, and then dried at 80°C for 18 h to obtain a ternary positive electrode material coated only with carbon quantum dots.
[0047] Comparative Example 4 Preparation of ternary positive electrode materials directly coated with carbon quantum dots and MOF (non-precursor).
[0048] According to the ternary positive electrode material LiNi in Example 1 0.8 Co 0.1 Mn 0.1 The preparation method of O2 obtains a ternary positive electrode material, and the precursor solution of MOF is stirred and reacted at 40°C for 24 hours to obtain a MOF solution.
[0049] The steps are basically the same as those in Example 1, except that the ternary cathode material is added to the carbon quantum dot solution for coating reaction, and then the MOF solution is slowly added dropwise to the mixed solution.
[0050] Comparative Example 5 Prepare a ternary positive electrode material that is first coated with MOF and then coated with carbon quantum dots.
[0051] According to the ternary positive electrode material LiNi in Example 1 0.8 Co 0.1 Mn 0.1 The preparation method of O2 obtains the ternary positive electrode material. The difference is that the ternary positive electrode material is first added to the MOF precursor solution, and then the carbon quantum dot solution is added for coating reaction.
[0052] Performance Testing: The materials prepared in Examples 1-2 and Comparative Examples 1-3 were respectively made into positive electrode sheets for lithium-ion batteries, and assembled into CR2032 button batteries for electrochemical performance testing.
[0053] The test results show that the composite materials of MOF and carbon quantum dots coated with ternary positive electrode materials prepared in Examples 1-2 have a first discharge specific capacity of 215 mAh / g and 210 mAh / g at a rate of 0.1 C, and after 100 cycles, the capacity retention rates are 93% and 92%, respectively.
[0054] The uncoated ternary cathode material of comparative example 1 has an initial discharge specific capacity of 180 mAh / g, and the capacity retention rate after 100 cycles is only 80%.
[0055] In comparative example 2, the ternary cathode material coated only with MOF has an initial discharge specific capacity of 190 mAh / g, and a capacity retention rate of 85% after 100 cycles.
[0056] In comparative example 3, the ternary positive electrode material coated only with carbon quantum dots has an initial discharge specific capacity of 195 mAh / g, and a capacity retention rate of 88% after 100 cycles.
[0057] In comparative example 4, the ternary cathode material directly coated with carbon quantum dots and MOF (non-precursor) has an initial discharge specific capacity of 188 mAh / g, and a capacity retention rate of 83% after 100 cycles.
[0058] In comparative example 5, the ternary positive electrode material first coated with MOF and then coated with carbon quantum dots has an initial discharge specific capacity of 189 mAh / g, and a capacity retention rate of 86% after 100 cycles.
[0059] It can be seen that the composite material of MOF and carbon quantum dots coated with the ternary cathode material prepared by the present invention has more excellent electrochemical performance.
[0060] The preparation method of the present invention is compared with the preparation of other methods: Enhanced structural stability: The carbon quantum dots prepared by the present invention work synergistically with MOF to help enhance the mechanical properties of the ternary cathode material, further stabilize the material structure, and inhibit structural changes during the charge and discharge process.
[0061] Improve electrochemical performance: It has good conductivity, can increase the electron transfer rate of the material, reduce the internal resistance of the battery, and work together with MOF to significantly improve the charge and discharge capacity, cycle stability and rate performance of the ternary positive electrode material.
[0062] Raw materials and preparation advantages: Common biomass such as glucose, sucrose or starch is used as raw material, and it can be prepared through relatively simple high-pressure reactor reaction and filtration steps. The raw materials are easy to obtain and the preparation method is relatively simple.
[0063] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a ternary cathode material coated with carbon quantum dots and MOF, characterized in that: The steps include: S1. Preparation of Carbon Quantum Dots The biomass solution is heated to react to obtain a carbon quantum dot solution; S2. Preparation of MOF precursor solution Dissolving the metal salt and the organic ligand in an organic solvent and stirring evenly to obtain a MOF precursor solution; S3, ternary cathode material coated with MOF and carbon quantum dots The ternary cathode material is added to the carbon quantum dot solution, and ultrasonic dispersion is performed to obtain a mixed solution; then the MOF precursor solution is added to the mixed solution, and the reaction is stirred to obtain a ternary cathode material coated with MOF and carbon quantum dots.
2. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S1, the biomass includes one or more of glucose, sucrose, and starch; And / or, the concentration of the biomass solution is 0.1-1 g / mL.
3. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S1, the heating reaction temperature is 180-240°C and the time is 4-12 h.
4. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S2, the metal salt includes nickel chloride.
5. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S2, the organic ligand includes 2,3,6,7,10,11-hexamidotriphenyl hexahydrochloride.
6. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S2, the molar ratio of the metal salt to the organic ligand is 1:1-1:3; And / or, in the MOF precursor solution, the concentration of the metal salt is 0.05-0.2 mol / L.
7. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S3, the ultrasonic dispersion time is 30-60 min.
8. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S3, the stirring reaction temperature is 25-80° C. and the time is 12-48 h.
9. The method for preparing a ternary cathode material coated with carbon quantum dots and MOF according to claim 1, characterized in that: In step S3, the usage ratio of the ternary positive electrode material, the carbon quantum dot solution, and the MOF precursor solution is 10-15 g: 100-150 ml: 100-150 ml.
10. Application of the ternary positive electrode material obtained by the preparation method as claimed in claim 1 in a lithium ion battery.
Citation Information
Patent Citations
Manganese-based metal organic framework compound-coated lithium ion battery ternary positive electrode material and preparation method thereof
CN107910529A
Method for coating and modifying ternary material by using carbon quantum dots
CN111430695A
Preparation method of Zn-based MOF electrode material coated ternary positive electrode material
CN112820867A
Preparation method of multi-metal MOF gradient coated modified ternary precursor
CN112993229A
Positive electrode material, preparation method thereof and lithium ion battery
CN116404135A
Cited By
Positive electrode material, positive electrode plate containing positive electrode material and electrochemical device
CN120453347A
Composite positive electrode material, preparation method thereof and positive electrode plate
CN120809803A